Vice and drug education and control: a textbook and review material - Dascil, Arlyn M.; Santos, Ronaldo Q. (Quezon City : Wisemans Books Trading, Inc, 2020)
"This humble manuscript is useful and is intended to serve as a guide to criminology students as well as to law enforcers, law practitioners as well as law students and crime investigators. Moreover, this manuscript contains questions that may be a useful guide for the reviewees during their preparation for the criminologists licensure examinations. The authors also incorporated here the provisions of R.A. No. 9165, otherwise known as the Comprehensive Dangerous Drugs Act of 2002."
Includes bibliographical references.
English text.
Keywords: Drug abuse--Philippines